P10: IBRUTINIB ASSOCIATED AUTOIMMUNE HEMOLYTIC ANEMIA. Issue 3 (23rd February 2016) - Datla, S; Draksharam, P; Sidhu, G
Abstract : Purpose of Study: Autoimmune hemolytic anemia (AIHA) is a common phenomenon in Chronic lymphocytic Leukemia (CLL)/Small Lymphocytic Lymphoma (SLL) accounting for about 4–7% of cases. AIHA is commonly associated with certain conventional chemotherapy agents used in CLL/SLL. Ibrutinib, bruton tyrosine kinase inhibitor is category 1 indication for high risk (del 17p) and relapsed/refractory CLL. Literature review reports 11cases of Ibrutinib associated AIHA. We report a case of AIHA precipitated by Ibrutinib in an high risk CLL patient, with prior history of AIHA. Methods Used: Patient is an 81 year old black man diagnosed with asymptomatic Stage I CLL (del 17p) in 2010 and was on active surveillance. He developed AIHA in 2012, with good response to steroids and Rituximab. Subsequently he received 8 cycles of rituximab for symptomatic CLL with resolution of symptoms. In 9/2014, noted to have progression of disease with worsening B symptoms, leukocytosis and lymphadenopathy. He was started on Ibrutinib 420 mg PO daily with regression of lymphadenopathy within 3 weeks of therapy, but presented with symptomatic anemia with hemoglobin of 3 gm/dl, positive direct Coomb's test, elevated reticulocyte count and LDH consistent with AIHA. WBC elevated at 360 K/uL from baseline of 150 K/uL and hemoglobin fell to 3 g/dl from 10 g/dl since Ibrutinib was initiated. Ibrutinib was held and patient received high dose prednisone followed by IVIG and cautious transfusion with minimal improvement in hemoglobin. Hemoglobin slowly up trended with weekly Rituximab and high dose steroids and remained stable around 10 gm/dl after 4 weeks of Rituximab. Ibrutinib was subsequently restarted with overall clinical improvement. Summary of Results: In our patient, occurrence of AIHA falls in between 2–4 weeks as other reported cases suggesting that Ibrutinib could be a likely precipitating factor. Conclusions: Review of data, reveals that 22% of patients had history of AIC prior to Ibrutinib, however occurrence of AIHA on Ibrutinib seems to be less common (0.7%).Mechanism of action of Ibrutinib associated cytopenias remains unclear. It was hypothesized that it may be due to IL-2 induced kinase inhibition by Ibrutinib, and needs further investigation.